KONSEP MUZIUM BARU: ANALISIS KRITIKAL PEMIKIRAN KOLONIAL TERHADAP BANGSA MELAYU - Abd Jalal, Ahmad Farid; Awang Pawi, Awang Azman; Abdul Rahim, Rahimin Affandi (JURNAL MELAYU SEDUNIA, 2020)
Construction of a new museum concept in Malaysia requires a clear understanding of the colonial scholarly theory that degrades the Malays and Islam. However, it can be seen that the museum institutions in our country are still trapped in the doctrine left by the colonialists from various aspects. Hence, the objective of this study is to debate the theories put forward by the French colonial empire in an effort to provide a solid framework for the construction of the new museum, which is detached from colonial influence. The methodology of this study is qualitative in nature, that is, with the method of analyzing the content obtained from primary sources and descriptively, then the sources are analyzed using the conceptual framework that has been developed. The results showed that the theories put forward by the colonials to the Malay world clearly has a negative impact on the spirit of the Malays today and biased in considering the subject of Malays in various aspects. Therefore, museum institutions play an important role as an educational medium to all walks of life and needs to undergo a transformation that is free from colonial influence. The colonial’s contributions to the development of our country today including the museum institutions that were inherited are undoubtedly large however in an order to build the spirits of the Malays, it is time that we rebuild our museum institutions with philosophies that are rooted in the Al-Quran and Sunnah.